2014
DOI: 10.1016/j.ymeth.2014.03.009
|View full text |Cite
|
Sign up to set email alerts
|

Measurements of behavioral quiescence in Caenorhabditis elegans

Abstract: The nematode Caenorhabditis (C.) elegans, a long time work horse for behavioral genetic studies of locomotion, has recently been studied for quiescent behavior. Methods previously established for the study of C. elegans locomotion are not well-suited for the study of quiescent behavior. We describe in detail two computer vision approaches to distinguish quiescent from movement bouts focusing on the behavioral quiescence that occurs during fourth larval stage lethargus, a transition stage between the larva and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
73
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(76 citation statements)
references
References 40 publications
3
73
0
Order By: Relevance
“…Recently, a biomechanical model was proposed in which a relaxed body posture with fewer body bends facilitates flipping of worms confined to a plane. Consistent with this result, ectopic flipping could be observed in a V-ATPase mutant that showed a relaxed body posture outside of lethargus (Iwanir et al, 2013; Nagy et al, 2014b; Schwarz et al, 2011, 2012; Tramm et al, 2014). We hence set out to directly test the idea that altered activity levels influence the probability that SIA activation leads to flipping.…”
Section: Resultssupporting
confidence: 76%
See 2 more Smart Citations
“…Recently, a biomechanical model was proposed in which a relaxed body posture with fewer body bends facilitates flipping of worms confined to a plane. Consistent with this result, ectopic flipping could be observed in a V-ATPase mutant that showed a relaxed body posture outside of lethargus (Iwanir et al, 2013; Nagy et al, 2014b; Schwarz et al, 2011, 2012; Tramm et al, 2014). We hence set out to directly test the idea that altered activity levels influence the probability that SIA activation leads to flipping.…”
Section: Resultssupporting
confidence: 76%
“…The occurrence of flips during periods of low mobility may seem counterintuitive at first, as flipping constitutes a motion and a flip could thus be, by definition, regarded as a motion bout. However, x-y movements of the nose and body typically define a motion bout (Iwanir et al, 2013; Nagy et al, 2014b). Flipping consists only of a rotation along the longitudinal axis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We used specialized microfluidic chambers designed to keep animals confined to an area within a camera field of view for recording the entirety of the lethargus period while still allowing animals to move freely within the chamber (Singh et al 2011). Surprisingly, when we observed locomotory quiescence during lethargus of wild-type animals ( Figure 4A) and vav-1 mutants ( Figure 4B), we found no difference in the total quiescence ( Figure 4D) or the duration of quiescence ( Figure 4E), unlike lethargus quiescence defective egl-30 mutants (Figure 4, C-E) (Schwarz and Bringmann 2013;Nagy et al 2014). Because ALA has been reported to play a minor role in lethargus quiescence (Van Buskirk and Sternberg 2007;Trojanowski et al 2015), we tested a mutant, plc-3, that has been shown previously to have a role in ALA to regulate quiescence during lethargus to determine whether our assay is sensitive enough to detect a minor lethargus quiescence defect.…”
Section: Vav-1 Function Is Dispensable For Sleep-like Behavior Duringmentioning
confidence: 75%
“…This concerns mice [12]- [14], Caenorhabditis elegans [15]- [17], as well as Drosophila flies [18]- [22]. However, to the best of our knowledge there is no system available for monitoring the behaviour of Drosophila at the larval states in culture vials for a long time period.…”
Section: Introductionmentioning
confidence: 99%